National trends of wrist arthroscopy in Italy: Analysis from 2001 to 2016 - Umile Giuseppe Longo; Rocco Papalia; Alessandro Mazzola; Sergio De Salvatore; Alessandro Tancioni; Valentina Piccioni; Alessandro deSire; Kristian Samuelsson; Stefano Zaffagnini; Ilaria Piergentili; Pieter D'Hooghe; Vincenzo Denaro (Journal of Experimental Orthopaedics)
Abstract Purpose This study aimed to evaluate the demographic features of patients undergoing wrist arthroscopy in Italy. A secondary aim was to perform an economic analysis of this type of surgery. Methods The National Hospital Discharge Records database was employed to conduct the analysis. Wrist arthroscopy surgical procedures were defined by the primary procedure code 80.23, according to the International Classification of Diseases, Ninth Revision–Clinical Modification code. Incidence rates were computed by dividing the number of annual cases by the size of the adult population reported annually by the National Institute for Statistics. Results 7875 wrist arthroscopy procedures were performed in Italy. The cumulative incidence rate was 1 for every 100,000 Italian residents. The need for wrist arthroscopy in Italy increased from 2001 to 2008 and then progressively declined up to 2016. The highest number of procedures was found between 40 and 49 years. Most patients undergoing wrist arthroscopy were females (50.6%). The mean age of patients was 41.6 ± 14.5. Wrist arthroscopy in Italy costs an average of 721,102 ± 171,195€ each year. Conclusions The incidence of this type of surgery peaked throughout the course of the 15 years, in 2006 and 2008. However, the number of procedures per 100,000 inhabitants has decreased since 2008. The economic analysis revealed that the cost of wrist arthroscopy is relevant to the healthcare system in Italy. Level of Evidence Level II.